Increased Endocytosis of Cadmium-Metallothionein through the 24p3 Receptor in an In Vivo Model with Reduced Proximal Tubular Activity - Zavala-Guevara, Itzel Pamela (Int J Mol Sci, 2021)
Background: The proximal tubule (PT) is the major target of cadmium (Cd(2+)) nephrotoxicity. Current dogma postulates that Cd(2+) complexed to metallothionein (MT) (CdMT) is taken up through receptor-mediated endocytosis (RME) via the PT receptor megalin:cubilin, which is the predominant pathway for reuptake of filtered proteins in the kidney. Nevertheless, there is evidence that the distal parts of the nephron are also sensitive to damage induced by Cd(2+). In rodent kidneys, another receptor for protein endocytosis, the 24p3 receptor (24p3R), is exclusively expressed in the apical membranes of distal tubules (DT) and collecting ducts (CD). Cell culture studies have demonstrated that RME and toxicity of CdMT and other (metal ion)–protein complexes in DT and CD cells is mediated by 24p3R. In this study, we evaluated the uptake of labeled CdMT complex through 24p3R after acute kidney injury (AKI) induced by gentamicin (GM) administration that disrupts PT function. Subcutaneous administration of GM at 10 mg/kg/day for seven days did not alter the structural and functional integrity of the kidney’s filtration barrier. However, because of PT injury, the concentration of the renal biomarker Kim-1 increased. When CdMT complex coupled to FITC was administered intravenously, both uptake of the CdMT complex and 24p3R expression in DT increased and also colocalized after PT injury induced by GM. Although megalin decreased in PT after GM administration, urinary protein excretion was not changed, which suggests that the increased levels of 24p3R in the distal nephron could be acting as a compensatory mechanism for protein uptake. Altogether, these results suggest that PT damage increases the uptake of the CdMT complex through 24p3R in DT (and possibly CD) and compensate for protein losses associated with AKI.